The influence of consumer sentiment and product quality on product brand image (case study of Ayam Geprek Basmallah) - M. Wahyu Maulana; Muhafidhah Novie (Institute of Computer Science (IOCS), 2024)
This study aims to determine the influence of consumer sentiment and product quality through online reviews on brand image in Ayam Geprek Basmallah Type of quantitative research with a descriptive approach. The research sample was 85 respondents. Data collection techniques using questionnaires. Data analysis techniques use path analysis. The results showed 1) brand image has a positive and significant influence on product quality. 2) Brand image has a positive and significant influence on online reviews.3) Consumer sentiment has a positive and significant influence on product quality.4) Consumer sentiment has a positive and significant influence on online reviews. 5)Online reviews have a positive and significant effect on product quality